Climate-smart agriculture as an investment destination for CSR - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The proceedings document the highlights of the Climate-Smart Agriculture and Corporate Social Responsibility workshop conducted by CCAFS South Asia, CIMMYT, BISA in partnership with the Federation of Indian Chambers of Commerce and Industry. Held in New Delhi, India, the event was a multi-stakeholder platform bringing together participants from academia, government and the private sector to discuss the scaling of climate finance through the Corporate Social Responsibility route for climate-smart agriculture in India.